2021
DOI: 10.3758/s13414-021-02254-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual timing precision with vibrotactile, auditory, and multisensory stimuli

Abstract: The growing use of vibrotactile signaling devices makes it important to understand the perceptual limits on vibrotactile information-processing. To promote that understanding, we carried out a pair of experiments on vibrotactile, auditory, and bimodal (synchronous vibrotactile and auditory) temporal acuity. On each trial, subjects experienced a set of standard intervals (400 ms each), followed by one interval of variable duration ( 400±1-80 ms). Intervals were demarcated by short vibrotactile, auditory, or bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Based on previous literature showing that multisensory effects are associated with medium and large effect sizes [69][70][71] , an a-priori sensitivity power analysis (G*Power 3 software 72 ) revealed that our sample size was large enough to detect within-between interactions of interest in a mixed-design analyses of variance (ANOVA) which corresponds to a medium f = 0.3 effect size with a statistical power (1-β) of 0.95 (given α = 0.05, a correlation between repeated measures of 0.5, number of groups = 2, number of measurements = 6).…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous literature showing that multisensory effects are associated with medium and large effect sizes [69][70][71] , an a-priori sensitivity power analysis (G*Power 3 software 72 ) revealed that our sample size was large enough to detect within-between interactions of interest in a mixed-design analyses of variance (ANOVA) which corresponds to a medium f = 0.3 effect size with a statistical power (1-β) of 0.95 (given α = 0.05, a correlation between repeated measures of 0.5, number of groups = 2, number of measurements = 6).…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that auditory temporal processing surpasses both tactile and visual temporal processing (Desloge et al, 2014;Jones, Poliakoff, & Wells, 2009;Rammsayer, 2014;Recanzone, 2003;Stauffer, Haldemann, Troche, & Rammsayer, 2012;Villalonga, Sussman, & Sekuler, 2021;Welch, DuttonHurt, & Warren, 1986).…”
Section: Visual and Vibrotactile Temporal Sensitivitymentioning
confidence: 99%
“…The pooling or combination of information from multiple sources has long been among neuroscience's major concerns (Chandrasekaran, 2017;Parker & Newsome, 1998;Sinnett, Soto-Faraco, & Spence, 2008). When those distinct sources are multiple sensory modalities, their interaction can take many different forms, including facilitative combination (Forster, Cavina-Pratesi, Aglioti, & Berlucchi, 2002;Sperdin, Cappe, Foxe, & Murray, 2009), destructive competition (Sinnett et al, 2008;Sun & Sekuler, 2021), compromise (Crommett, Madala, & Yau, 2019), and unimodal dominance (Burr, Banks, & Morrone, 2009;Colavita, 1974;Villalonga et al, 2021). With one exception, these studies did not explicitly require temporal judgments.…”
Section: Experiments 2: Unimodal and Bimodal Temporal Sensitivitymentioning
confidence: 99%
“…It is well established that auditory temporal processing surpasses both tactile and visual temporal processing (Desloge et al, 2014 ; Jones et al, 2009 ; Rammsayer, 2014 ; Recanzone, 2003 ; Stauffer et al, 2012 ; Villalonga et al, 2021 ; Welch et al, 1986 ). Fewer psychophysical studies have directly compared tactile and visual temporal processing, and these visuo-tactile comparisons yield mixed results.…”
Section: Introductionmentioning
confidence: 99%